Necrobiosis lipoidica diabeticorum: A case-based review of literature - Kota, Sunil Kumar (Medknow Publications & Media Pvt Ltd, 2012)
Necrobiosis lipoidica diabeticorum (NLD) is a rare chronic and granulomatous skin disorder that affects 0.3% of diabetic patients. Although the etiology and pathogenesis of NLD is still controversial, it is thought that microangiopathy has an important role. The legs are the most common site for NLD, but involvement of other areas such as the abdomen, upper extremities and scalp has been reported. There is no rational therapy. However, benefit has been reported from different treatment regimens such as drugs acting on the hemostatic mechanisms, corticosteroid therapy (topical, intralesional and systemic), enhancers of wound healing, surgery and immunomodulating therapies (including photochemotherapy). We report a 59-year-old female, who was a diabetic patient with multiple, disseminated lesions on the legs, which tended to disappear as the glycemic control was achieved. Hereby, we also review the existing literature for the evolving aspects of etiopathogenesis and treatment.